Periods in African Literature: A Survey of Evolution - Nwaukoni, Anthonia; Usobunandu Anukwu, Anthonia (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
African literature is characterized by different historical events which have ended up creating a kind of seams on its polity, thus leading to its categorization by periods, factors and times. The features of each period are uniform and peculiar which are reflected in the theme and style of the writers. This paper aims at defining different periods in African literature and the factors that influence the writers of each period. This is achieved by looking at various events in history and studying the works of different authors including articles. Among other things, the paper reaffirms that there are three distinct periods in African literature: the colonial, the post-colonial, the contemporary time and that each of them is based on the realities of its time.